Isolation and characterisation of nanofibrillated cellulose from N36 Ananas comosus leaves via ball milling with green solvent - Surenthiran, Gnanasekaran; Noor Ida Amalina, Ahamad Nordin; Saidatul Shima, Jamari; Jun Haslinda, Shariffuddin (Elsevier Ltd, 2022)
The production of valuable materials from biomass into nanosized become the principal focus of the developing industries on achieving green-based composite product, designed for extensive range of applications. This study principally, focused on discovering green method for the utilisation of N36 Ananas comosus leaves fibre (PALF) to highly potential material. Nanofibrillated cellulose (NFC) were successfully isolated from PALF by ball milling with presence of isopropyl alcohol. The effect of isopropyl alcohol and the milling time on nano fibrillation were analysed through characterisation of NFCs including Field Emission Scanning electron microscopy (FESEM), Xray diffraction (XRD), thermogravimetric analysis (TGA), Zeta-potential (ZP), Fourier transform infra-red (FTIR) and Particle size analysis (PSA). Comparatively, the 1:4─15 min NFC sample which milled for 15 mins with 1 mL of cellulose suspension and 4 mL of IPA, express desirable features in the concern of morphology, fibre size, yield, crystallinity, thermal stability, and homogeneity on disintegration of PALF fibre. High thermal degradation temperature of 323 ℃ and crystallinity index of 67%, reveal the potential on reinforcing to improve the composite’s thermal stability and mechanical properties. Moreover, it exhibits excellent surface morphology, stability with low self-agglomeration, and uniformity in defibrillation with fibre diameter of 25.84 ± 8.30 nm, zetapotential of − 32.31 ± 2.51 and PDI of 0.103. Besides, the high yield of NFC (>90%), increase the feasibility of NFC production. Hence, addition of IPA gives significant impact on defibrillation by disrupt the intermolecular hydrogen bond, so that less milling time is convenient on production of NFC without causes severe damage on other properties.